Mobile Game-based Learning for Online Assessment in Collaborative Learning - Yasmin Khairani Zakaria, Nur; Zaini, Hafiz; Hamdan, Fairus; Norman, Helmi (International Journal of Engineering and Technology, 2018)
Mobile technologies have impacted the educational scenario by allowing connectivity and seamlessness in teaching and learning. Previous studies have indicated that there is a lack of studies on mobile game-based learning, especially in real time blended learning settings. In addition, previous researches have also indicated that competitive aspect is able to enhance the learning process. As such, to solve the problems and fill the gaps, we investigated mobile game-based learning in an ethnic relations course at higher educational settings. The software used was Kahoot and it allowed assessing students’ achievement via a mobile game-based learning approach. The approach applied was single-group experiment using a massive open online course (MOOC) on ethnic relations. We analyzed the achievement of students using mobile game-based learning and assess after pre- and post-sessions in a period of two months. Findings show that there are three types of learners in mobile game-based learning which are: high achievers, gradually-increasing achievers, and gradually-decreasing achievers. Findings also indicate that mobile-game based learning can potentially be used for promoting engagement in learning. In sum, the paper showed that there are different type of learning in mobile game-based learning and it can be used to increase the level of engagement in learning.